2022
DOI: 10.4103/jfmpc.jfmpc_2362_21
|View full text |Cite
|
Sign up to set email alerts
|

Role of MRCP to determine the etiological spectrum, level and degree of biliary obstruction in obstructive jaundice

Abstract: Context: Obstructive jaundice as a result of hepatocellular disease many a times is indistinguishable from jaundice due to extrahepatic biliary obstruction based on just clinical and biochemical examinations. It is one of the most frequent and grave form of hepatobiliary disease which may lead to complications like ascending cholangitis, malabsorption and hepatorenal syndrome, thus demanding urgent surgical intervention. Thus not only early diagnosis but also accurate identification of level and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Chinese center over a period of 14 years. Smaller retrospective cohort studies conducted across Europe, Australia, Central Asia and South Asia have provided valuable insights into obstructive jaundice [16][17][18][19][20][21][22]. Notably, Garcea et al's retrospective analysis of over 1000 cases in the United Kingdom found similar disease patterns to ours, with CBD stones and pancreatic ductal adenocarcinoma as primary benign and malignant etiologies, respectively [19].…”
Section: Discussionsupporting
confidence: 60%
“…Chinese center over a period of 14 years. Smaller retrospective cohort studies conducted across Europe, Australia, Central Asia and South Asia have provided valuable insights into obstructive jaundice [16][17][18][19][20][21][22]. Notably, Garcea et al's retrospective analysis of over 1000 cases in the United Kingdom found similar disease patterns to ours, with CBD stones and pancreatic ductal adenocarcinoma as primary benign and malignant etiologies, respectively [19].…”
Section: Discussionsupporting
confidence: 60%
“…Expert gastroenterologist and radiologist along with a trained team is needed for the ERCP and procedure is done under sedation or general anesthesia. 5,6 Despite its usefulness, the procedure of ERCP is however related to some unwanted complication which includes sepsis, bleeding, bile leakage, pancreatitis and even a reported rate of mortality up to 1%. 7 A procedure called magnetic resonance cholangiopancreatography (MRCP) introduced in 1991 is now under frequent use for diagnostic purposes in the pathologies related to pancreatic duct and hepatobiliary diseases.…”
Section: Introductionmentioning
confidence: 99%